Women’s Leadership Trends in Tribal Enterprises-A Study in Cooperatives Based Tribal Enterprises in Jharkhand, India - Bhaskar, Prem; Kaushik, Madhulika (International Journal of Multidisciplinary: Applied Business and Education Research, 2022)
This paper attempts to analyse the status of women entrepreneurship initiatives through cooperatives in Jharkhand, India and highlights the impact on tribal women empowerment, and their leadership competencies on this economic contribution. Bargaining for women leadership positions in all spheres of Asian societies has emerged as an important concern in quest of equity, whereas tribal women’s development has mostly remained limited to their participation in various programmes run by the government as well as non-government agencies. Recognition of women leaders from a tribal community in the 21st century is still a distant dream. Yet economic empowerment and group activities in the tribal regions of Jharkhand have revealed the potential and are seen as instrumental in transforming leadership capabilities of tribal women leaders in the tribal geography of Jharkhand. The paper shares the outcomes of the author’s study based on case studies in the region, secondary data and, literature review, related to the trends in tribal women’s leadership. The study reveals that women from tribal communities of Jharkhand have traditionally been disempowered socially and treated as less capable to lead and mostly refrained from societal leadership positions. It is also revealed that with facilitation and support, they demonstrate excellent leadership competencies to manage successful collective enterprises. The study also raises prominent questions of assessing the impact and influence of such empowerment and collective entrepreneurship on socioeconomic aspects.